การพัฒนาชุดกิจกรรมการเรียนรู้การอ่านเพื่อความเข้าใจตามแนวสมดุลภาษาสำหรับนักเรียนประถมศึกษา - สุวกาญจน์ ทาวี (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The purposes of this research were 1) to develop a reading comprehension learning package based on the balanced literacy approach for elementary school students, and 2) to study the reading comprehension before and after participating in learning activities. The participants consisted of 28 fourth-grade Thai students. The research instruments were 1) a learning package based on the balanced literacy approach for elementary students; 2) a reading comprehension test; and 3) a student reading behavior observation form. The statistics used in the research were the Mean (M) and Standard Deviation (SD) and dependent simple t-test. The results of this research were as follows: 1) The key elements of the learning package based on a balanced literacy approach for elementary students consisted of (1) Learning package manual, (2) Lesson plans consisted of 4 components; (2.1) Learning activity step, (2.2) The forms of assessment for learning, (2.3) reading materials, and (2.4) the evaluation approach. 2) students’ level of reading comprehension abilities was also higher after using a package based on a Balanced literacy approach at the .05 level of significance.